Relational State Capacity: Conceiving of Relationships as a Core Compo nent of Society’s Ability to Achieve Collective Ends - Honig, Dan; Krishnamurthy, Mekhala; Sharma, Rahul Karnamadakala (Johns Hopkins University, 2025)
Relational state capacity (RSC) integrates the quality of citizen-stat e relationships into the concept of state capacity, emphasizing mutual recognition between citizens and state agents as foundational for soc ietal problem-solving. Traditional state capacity definitions overemph asize technical and institutional elements, overlooking relational dyn amics. RSC is a latent societal resource activated through mutual reco gnition in citizen-state exchanges with potential to improve outcomes across diverse domains, from public health to social cohesion. We have for too long transactionalized governance; we need instead to collect ively invest in intentional structures and practices that foster relat ionality. Drawing on insights from existing literature, the paper expl ores how RSC is built, intermediated, and shaped by broader societal n orms and organizational dynamics. By making RSC legible as an object o f inquiry, the paper lays the groundwork for empirical investigation i nto RSC’s causal pathways, spillover effects, and resilience to disrup tion. There are many pathways for theoretical and empirical developmen t in this emergent field; focusing on the relational in understanding state performance has the potential to enhance citizens’ welfare, stre ngthen democratic resilience, and improve public sector performance.